2000
DOI: 10.1001/archinte.160.22.3424
|View full text |Cite
|
Sign up to set email alerts
|

A Search for Sex Differences in Response to Analgesia

Abstract: Our results demonstrated no sex effect on the analgesic response to ibuprofen. These results were obtained under the post-third-molar extraction setting, in which the least possible confounding factors are present. To fully establish the generality of this phenomenon, studies should be carried out in other pain models and using analgesic medications with different mechanisms of action. Arch Intern Med. 2000;160:3424-3428.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(30 citation statements)
references
References 31 publications
2
27
0
1
Order By: Relevance
“…Gender differences have been observed in response to acute pain in the dental pain model with ibuprofen being more effective in men than in women (Walker and Carmody 1998). Other studies using a similar third molar extraction dental pain model have not revealed any gender differences in response to analgesia with ibuprofen (Averbuch and Katzper 2000). Aside from these factors it appears therefore that variability in response to analgesia with ibuprofen may relate to acute pain and altering the pharmacokinetics of the drug and possibly gender differences.…”
Section: Relief Of Pain Inflammation and Fevermentioning
confidence: 98%
“…Gender differences have been observed in response to acute pain in the dental pain model with ibuprofen being more effective in men than in women (Walker and Carmody 1998). Other studies using a similar third molar extraction dental pain model have not revealed any gender differences in response to analgesia with ibuprofen (Averbuch and Katzper 2000). Aside from these factors it appears therefore that variability in response to analgesia with ibuprofen may relate to acute pain and altering the pharmacokinetics of the drug and possibly gender differences.…”
Section: Relief Of Pain Inflammation and Fevermentioning
confidence: 98%
“…In general, there is no difference in analgesic responses to ibuprofen between male and female patients when managing post-operative pain. 36 Metaanalyses indicate that ibuprofen produces greater analgesia than paracetamol/codeine combinations. 17 Another meta-analysis of ibuprofen 37 indicated that it produces a dose-related analgesia over the range of 200-800mg, as shown in Fig 1. Thus, increasing the dose of ibuprofen will produce an increasing magnitude of analgesia.…”
Section: Trials/efficacymentioning
confidence: 99%
“…57 In addition, a meta-analysis of third molar extraction studies concluded that women report significantly greater pain levels compared with men. 36 Given these factors, clinicians should prescribe drugs based on the patient's reported pain levels. Although a patient's report of pain is not an exact value, it is a useful alternative to prescribing fixed doses to all patients as this invariably leads to some being over-medicated and others experiencing unnecessary pain due to being under-medicated.…”
Section: The Opioids (Narcotics) Mechanismsmentioning
confidence: 99%
“…( Fig. 5, 6, 7, 8) In a study conducted on the effects of analgesics on gender, it was found that when ibuprofen was given for moderate to severe dental pain, there were no gender differences 14 . Hence gender of the patient plays a very small role in influencing the choice of analgesic unless the patient happens to be pregnant, lactating etc.…”
Section: Resultsmentioning
confidence: 99%